2015
DOI: 10.5935/0103-5053.20150111
|View full text |Cite
|
Sign up to set email alerts
|

Simple Methods via Mid-IR or1H NMR Spectroscopy for the Determination of the Iodine Value of Vegetable Oils

Abstract: Two methods for determining the iodine value in vegetable oils are described. One employs mid-infrared (mid-IR) spectroscopy and the other uses hydrogen nuclear magnetic resonance ( 1 H NMR). The determination of the iodine value is based on either the transmittance intensity of mid-IR signals or on the 1H NMR signal integration and multivariate calibration. Both of the methods showed adequate coefficients of determination (r 2 = 0.9974 and 0.9978, respectively) wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 4 publications
1
8
0
Order By: Relevance
“…After machining, the oils' spectra showed the same tendency of variation as that of the sunflower oil, as shown in Figure 2b- The FTIR spectra registered for the sunflower oil revealed that there were no appreciable differences in the spectral features before and after processing, as well as between different working regimes, apart from changes in the intensity of some absorption bands; the most relevant change was within the range of 1465-721 cm −1 , where an increase in the absorbance of the oil corresponding to the middle intensive working regime (E1181) and a slight decrease of the absorbance of the oil corresponding to the most intensive working regime (E1191), were recorded. The obtained spectra are in very good agreement with those presented in the literature [32].…”
Section: Spectra Analysis Of the Dielectric Fluidssupporting
confidence: 90%
“…After machining, the oils' spectra showed the same tendency of variation as that of the sunflower oil, as shown in Figure 2b- The FTIR spectra registered for the sunflower oil revealed that there were no appreciable differences in the spectral features before and after processing, as well as between different working regimes, apart from changes in the intensity of some absorption bands; the most relevant change was within the range of 1465-721 cm −1 , where an increase in the absorbance of the oil corresponding to the middle intensive working regime (E1181) and a slight decrease of the absorbance of the oil corresponding to the most intensive working regime (E1191), were recorded. The obtained spectra are in very good agreement with those presented in the literature [32].…”
Section: Spectra Analysis Of the Dielectric Fluidssupporting
confidence: 90%
“…In the spectrum of chia oil in Figure A, the assigned numbers 3, 4, 6, 7, 9, and 10 correspond to the olefinic signals from the hydrogens on the fatty acid tails . These signals are evident in both the linolenic and linoleic fatty acid tails.…”
Section: Results and Discussionmentioning
confidence: 99%
“…The FTIR-ATR spectrum of tucuma oil, PCL and PCL + tucuma oil are shown in Figure 2 and it contains characteristics bands of a vegetable oil [42][43][44][45] . These bands are described in Table 2, according to the findings of Leonardi et al [42] , Ali et al [44] and Gomez et al [45] .…”
Section: Resultsmentioning
confidence: 99%